2015
DOI: 10.1007/s11249-015-0629-8
|View full text |Cite
|
Sign up to set email alerts
|

A Semi-deterministic Wear Model Considering the Effect of Zinc Dialkyl Dithiophosphate Tribofilm

Abstract: Tribochemistry plays a very important role in the behaviour of systems in tribologically loaded contacts under boundary lubrication conditions. Previous works have mainly reported contact mechanics simulations for capturing the boundary lubrication regime, but the real mechanism in which tribofilms reduce wear is still unclear. In this paper, the wear prediction capabilities of a recently published mechanochemical simulation approach (Ghanbarzadeh et al. in Tribol Int, 2014) are tested. The wear model, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 49 publications
(72 reference statements)
3
69
0
1
Order By: Relevance
“…The same trends were proposed by Cen et al [7] and Ghanbarzadeh et al [8]. On the other hand, the increase in the wear in the presence of water can be attributed to the higher tribocorrosion rate of steel substrate which then results in the more availability of iron ions in the glassy phosphate tribofilm.…”
Section: Effect Of Relative Humidity On Tribochemistrysupporting
confidence: 80%
See 1 more Smart Citation
“…The same trends were proposed by Cen et al [7] and Ghanbarzadeh et al [8]. On the other hand, the increase in the wear in the presence of water can be attributed to the higher tribocorrosion rate of steel substrate which then results in the more availability of iron ions in the glassy phosphate tribofilm.…”
Section: Effect Of Relative Humidity On Tribochemistrysupporting
confidence: 80%
“…It was shown that the wear behaviour of the tribological system depends on the properties of the reaction layer formed on the surface. [4,[6][7][8].…”
Section: Effect Of Water On Decomposition Of Zddp (Zinc Dialkyl Dithimentioning
confidence: 99%
“…It has been hypothesized that the balance between formation and durability of the tribofilm significantly affects the wear performance of the tribological system [23,35,37]. To investigate this, a set of experiments was designed to study the durability of the tribofilm.…”
Section: Methodsmentioning
confidence: 99%
“…The hypothesis was based on the experimental observations of removal of the tribofilm and wear of the system even in the presence of fully-formed tribofilms [17,31,36]. The wear hypothesis was then validated against some wear measurements in experiments [37,38] and has shown good agreement.…”
Section: Growth Of Zddp Tribofilmmentioning
confidence: 99%
“…In the current study, a new part is added to the original model to include the effect of water concentration by using two approaches explained bellow. Although the model components are explained briefly in this section, the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 6 details of the contact model and the wear mechanism can be found in Ref (31) and (32) respectively.…”
Section: Numerical Approachmentioning
confidence: 99%